The use of the C-eye system in communication and education of children - Zawichrowska, Marta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
During working with children with communication disorders, they are more and more often accompanied by devices supporting the development of speech. One of them is the C-eye system, which is used especially in two areas – communication and education. This article is an introductory report on the research on the use of high technologies in working with children with developmental disorders, accompanied by deficits in the field of verbal speech. The described case study concerns a child with delayed speech development, without any additional health burden, in whom the etiology of communication disorders has not been determined despite careful diagnostics and many specialist consultations. The article was written on the basis of observations, an interview with the family and the recommendations provided, and presents the original path of therapeutic treatment with the use of the C-eye device, which can be used in work with preschool and early school children. Very important was the neurologopedic diagnosis and research conducted during the therapy, which allowed for the proper definition of therapeutic goals and showed its effectiveness, both in the communication, educational and social sphere.